2016
DOI: 10.1051/epjconf/201612204004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and analysis of nucleon emission from deuteron-induced reactions at incident energies up to 100 MeV

Abstract: Abstract.We have so far developed a computational code system dedicated to deuteroninduced reactions in combination with some theoretical models. In our previous works, the code system was successfully applied to systematic analyses of double-differential cross sections (DDXs) of (d,xp) reactions for 12 C, 27 Al, and 58 Ni at incident energies up to 100 MeV.In the present work, we apply the code system to neutron emission from deuteron-induced reactions. Since there is few experimental data of DDXs of (d,xn) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…One of the main purposes to develop DEURACS was to contribute to the design study of intensive neutron sources using deuteron accelerators. Hence, DEURACS had been mainly applied to analysis of double-differential cross sections of the (d, xn) and (d, xp) reactions and the calculated results were in good agreement with the experimental data up to 50 MeV/nucleon especially at forward angles [19][20][21][22][23][24]. From these analyses it was concluded that the models implemented in DEURACS to calculate the breakup processes are valid in the energy range since the nucleon emission at forward angles has a large sensitivity to treatment of the breakup processes.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…One of the main purposes to develop DEURACS was to contribute to the design study of intensive neutron sources using deuteron accelerators. Hence, DEURACS had been mainly applied to analysis of double-differential cross sections of the (d, xn) and (d, xp) reactions and the calculated results were in good agreement with the experimental data up to 50 MeV/nucleon especially at forward angles [19][20][21][22][23][24]. From these analyses it was concluded that the models implemented in DEURACS to calculate the breakup processes are valid in the energy range since the nucleon emission at forward angles has a large sensitivity to treatment of the breakup processes.…”
Section: Introductionmentioning
confidence: 92%
“…The deuteron is a weakly bound nucleus and easily breaks up by the interaction with a target nucleus. By previous experimental [4][5][6][7][8][9][10] and theoretical [11][12][13][14][15][16][17][18] studies including ours [19][20][21][22][23][24], it is well-known that breakup processes play a significant role in the secondary nucleon emission from deuteron-induced reactions. Similarly, the breakup processes are expected to have some influence on spallation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, we have so far developed an integrated code system dedicated for theoretical analysis and prediction of deuteron-induced reactions, which is called DEUteron-induced Reaction Analysis Code System (DEURACS) [6][7][8][9][10][11]. DEURACS consists of several calculation codes based on theoretical models to describe respective reaction mechanisms characteristic of deuteron-induced reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have so far focused on nucleon emission from deuteron-induced reactions and examined the applicability of DEURACS to such reactions. In our previous work, DEURACS was successfully applied to analyses of DDXs for (d,xp) reactions at incidenet energies of 56 and 100 MeV [6][7][8], activation cross sections by (d, p) reactions from threshold to 50 MeV [7][8][9], and double-differential thick target neutron yields (TTNYs) from (d,xn) reactions up to 50 MeV [10,11]. Note that other microscopic calculations of inclusive (d,xp) reactions have been recently reported by other research groups [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…This BU + DR analysis was completed by PE + CN contributions provided by the exciton and Hauser-Feshbach statistical models. DDX data integrated over the outgoing energy, for incident energies from 56 to 100 MeV, were similarly analyzed as well as angular-distributions for the 12 C(d, n) 13 N reaction at incident energies from 7 to 18 MeV [42]. Of particular interest has been a similar, even if less clear, energy dependence of the spectroscopic factors extracted from DWBA analyses for the (d, p) reaction on all the four target nuclei, under the assumption that the incidentenergy dependence is same for all final states.…”
Section: Deuterons On Light Nucleimentioning
confidence: 99%